INVESTIGATING THE ADVANTAGES OF BILINGUALISM: MULTIDIMENSIONAL RESEARCH FINDINGS - Gusti Putu Rustika Dewi; Putu Kerti Nitiasih; Luh Putu Artini; Ni Komang Arie Suwastini; Novi Diah Haryanti (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
Bilingualism is a widely discussed phenomenon due to its rising trend in this globalization era. Many negative conclusions about bilingualism have been met with positive outcomes from recent studies. This study was library research aimed at exploring the advantages of bilingualism in terms of cognitive, socio-emotional, as well as academic and career advantages of bilingualism as proven by previous studies published in reputable international journals indexed by Scopus or WoS from 2015 to 2020. The critical review revealed that bilingualism provides cognitive, socio-emotional, academic and career advantages. In terms of cognitive advantages, bilingualism contributes to better executive functioning and working memory and delaying the cognitive aging disease. Socio-emotionally, bilingualism promotes self-confidence, empathy, friendliness, communicative skills, and a more open-minded attitude toward cultural differences, respect toward speakers of other languages. Academically, bilinguals show higher achievement, while career-wise, there is a high preference for companies to hire bilinguals and a high possibility of getting promotions. These conclusions imply that early exposure to bilingualism provides opportunities for children to develop their cognitive and socio-emotional better that contribute to their academic and career.